Transcriptome profiling of omental adipose tissues in human obesity by rna-seq / Ng Hien Fuh - Ng , Hien Fuh (2015)
Recent scientific research has indicated that inflammation in adipose tissues plays a central role in the pathophysiology of obesity and related complications. However, despite extensive studies, the molecular mechanisms that trigger and aggravate the obesity-related inflammation remain unclear. In this study, transcriptome profiling of omental adipose tissues from three obese and four lean patients was performed using the RNA-Seq technology. Differential expression analysis identified 206 dysregulated genes (p-value < 0.05 and fold change ≥ 2) in obesity, that are known to be involved in a multitude of functions including stress response, inflammatory response and leukocyte adhesion. Furthermore, differential splicing analysis uncovered a possible role for TLR4 RNA splicing in obesity, which is further validated with an independent cohort of samples (five obese and six lean patients) using RT-qPCR. These findings suggest that, as a person experiences weight gain leading to obesity, the adipose splicing pattern of TLR4 transcripts changes in favor of activation of TLR4 signaling, which in turn, may contribute to the progression of obesity-related inflammation and complications. This study provides a glimpse at the transcriptome of disease-state adipose tissue in obesity, and demonstrates the potential importance of aberrant RNA splicing and expression in obesity-associated immune dysregulation.